Peningkatan Kapasitas Aparatur Pemerintahan Desa dan Masyarakat melalui Pelatihan Administrasi Pemerintahan di Desa Sukamenak Kecamatan Cikeusal Kabupaten Serang (Faculty of Social Science, Universitas Negeri Semarang, 2018)
The purpose of this community service activity is to provide training on village government administration and village financial reporting governance in improving the capacity of village government apparatus. It is hoped that through these activities it will promote accountable and transparent village governance and give birth to village cadres who have good knowledge, attitude and skills. While the activity method used is Participatory Learning And Action. This activity is conducted by emphasizing on lecture, discussion, brainstorming conducted interactively with group members and continued with action or real activity that relevant with material of society empowerment. The results of community service activities run in accordance with predetermined plans, the community has a response and enthusiasm for training and created changes in knowledge, attitudes and skills.